Social protection in humanitarian contexts: Exploring stakeholder views from Zambia - Liana Chikwekwe; Sydney Sihubwa; Muchimba Sarah Siamachoka; Roosa Lambin; Milla Nyyssölä; Rodrigo Carvalho Oliveira (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
This study explores the social protection and humanitarian emergency nexus in Zambia. Drawing on 25 stakeholder interviews and relevant literature sources, it seeks to (i) identify the social protection needs experienced in the country in the context of different shocks and crises; (ii) elucidate the current barriers to effective delivery of social protection arrangements and their expansion to better respond to humanitarian contexts; and (iii) map views on the ground concerning opportunities and ways forward in pursuit of a shock-responsive social protection system. The results show that Zambia is moving towards a better integrated social protection system with a number of shock-responsive elements. However, stakeholders highlight the acute need for horizontal and vertical expansion of social assistance; better use of existing meteorological and social data to design context-sensitive interventions; strengthening domestic financing mechanisms and legislation to enhance sustainability of social protection provision; and, more generally, moving towards a better coordinated, synergic and anticipatory model of policy-making and social protection delivery that effectively responds to humanitarian emergencies.
Keywords: I38; O15; Q54; 330; social protection; humanitarian contexts; shock-responsive; Zambia